As condições de trabalho e a satisfação profissional: dimensões do profissionalismo docente no ensino médio - Souza, Gelza Lúcia de Brito (2009)
The dissertation is developed in the Research Base of Teacher Training and Professionalization of Universidade Federal do Rio Grande do Norte as a way to discuss the professionalization of High School teachers in Natal. It is a study linked to the research The context of teaching practice and professionalism: the case of high school teachers and sponsored by CNPq, with the objective of characterizing working conditions and job satisfaction as dimensions to the teacher professionalism in high schools. In this study we prioritized the focus on professionalization in national and international discussions, which combines the aspects of teaching in its historical, social, political and economical path, in order to reflect about its evolutional elements in the hierarchy of professions and establish a relation to high school teaching. To develop this relation we elaborated some questions that are considered relevant, such as: How does the high school teacher evaluate his/her working conditions to his/her professional practice? What level of satisfaction does the high school teacher have regarding his/her professional practice? What expectations does the high school teacher have in relation to his/her professional development? The answers to those questions were according to the high school teachers considerations shown in the questionnaire, which was structured with open and closed questions. These questions gave better adequacy to the teachers evaluations about their working place and the situations they experience in their working conditions, provoking job satisfaction and expectations for professional growth. The description of the teachers perception about working conditions, job satisfaction and expectation of professional development can explain the distinct factors that characterize these categories in the working context, although the conclusive results, in general, do not show a direct relationship between the categories studied. Some factors that teachers attribute as causes of bigger difficulties in working conditions and work activity itself are: working time, salary, professional status, school s infrastructure, and school s social context. These factors are similarly related to the degree of job satisfaction, without showing interference in the professional expectations